Tanzania agricultural policy profile - Rweyemamu, M. R.; Mruma, T.; Nkanyani, S. (International Water Management Institute (IWMI), 2024)
Tanzania places a significant emphasis on the importance of its agricultural sector, acknowledging its pivotal role in both the economy and the livelihoods of its citizens. The government's commitment to the advancement of agriculture is evident through the execution of diverse policies and programs. The central pillar of Tanzania's agricultural policies is the Agricultural Policy of 2013, which delineates strategies to boost productivity, ensure food security, and enhance the socio-economic conditions of farmers. The policy underscores the importance of sustainable practices and the adoption of technology.